Impact of Combined Application of Cold Compression and Abdominal Binder as a Pain Management Method on Pain Levels and Postoperative Ambulation in Gynaecological Patients Having Undergone Open Abdominal Surgery - Inthiyot, Ketsarin; Chanruangvanich, Wallada; Wongkongkam, Kessiri; Oranratanaphan , Shina (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To examine pain level and postoperative ambulation of gynecological patients having undergone open abdominal surgery after having been treated with a pain management programme that conjointly applied cold compression and an abdominal binder Design: Cluster randomised controlled trial Methodology: The participants were gynecological patients having undergone open abdominal surgery aged between 18-69 years. They were randomly assigned into experimental and control groups, 25 in each. During the three-day experiment, the experimental group received the pain management programme that conjointly applied cold compression and abdominal binders, whilst the control group received standard care. The Visual Analog Scale (VAS) was used to assess the participants’ pain levels. Then, on day 1 after the surgery, measurement of the participants’ ability to sit up in the bed, move down to sit beside the bed, and walk around the bed, as well as the distance of their first walk, was undertaken using a stopwatch with a walking distance measuring mode and entered into a postoperative ambulation assessment form. The data were analysed using descriptive statistics, a Chi- square test, a Mann-Whitney U test, and repeated measures ANOVA. Results: Having received the pain management programme, the experimental group displayed a significantly lower pain level after sitting up in the bed, moving down to sit beside the bed, and walking around the bed, than the control group did. Besides, the interaction between the programme and the measurement time had a statistically significant effect on the pain levels (p < 0.01). Also, the experimental group’s distance of their first walk around the bed and duration of their sitting up in bed were significantly greater than the control group’s (p < 0.05). Recommendations: Combined application of cold compression and an abdominal binder to pain management is recommended as an effective means of pain control in gynaecological patients, to promote the early ambulation ambulation and recovery after surgery.